Graphic design school : the principles and practice of graphic design - Dabner, David; Swann, Alan, 1946- (New Jersey : Wiley, 2014)
"Graphic Design School allows students to develop core competencies while understanding how these fundamentals translate into new and evolving media. With examples from magazines, websites, books, and mobile devices, the Fifth Edition provides an overview of the visual communications profession, with a new focus on the intersection of design specialties. A brand-new section on web and interactivity covers topics such as web tools, coding requirements, information architecture, web design and layout, mobile device composition, app design, CMS, designing for social media, and SEO"--
"The Fifth Edition provides an overview of the visual communications profession, with a new focus on the intersection of design specialties. A brand-new section on web and interactivity covers topics such as web tools, coding requirements, information architecture, web design and layout, mobile device composition, app design, CMS, designing for social media, and SEO"--
Originally published: Graphic design school. 1991.
"A quarto book."
Includes bibliographical references (pages 202-203) and index.
Keywords: Graphic arts; Commercial art; DESIGN / Graphic Arts / General